Efektivitas Upaya Komisi Pemilihan Umum Dalam Meningkatkan Partisipasi Politik Masyarakat Kota Gorontalo pada Pemilu 2024 - Umar, Sri Rahayu; Rahim, Erman I.; Moha, Mohamad Rivaldi (Universitas Muhammadiyah Kotabumi, 2025)
This study is titled “The Effectiveness of the General Elections Commission’s Efforts in Increasing Political Participation of Gorontalo City Residents in the 2024 General Election.” The aim of this research is to assess the extent to which the General Elections Commission (KPU) has effectively enhanced political participation among citizens and to identify the factors influencing such participation. An interdisciplinary approach was employed as the research method.The findings indicate that although the KPU has carried out its duties in accordance with Law Number 7 of 2017, its effectiveness remains suboptimal. Some citizens still lack clear access to information and express dissatisfaction with the available candidates. Furthermore, political apathy, low public trust in the political system, and sudden regulatory changes serve as barriers to participation. These issues have negatively impacted public engagement in the democratic process.